Zinc‐Catalyzed Asymmetric Formal [4+3] Annulation of Isoxazoles with Enynol Ethers by 6π Electrocyclization: Stereoselective Access to 2H‐Azepines - Zhu, Xin‐Qi; Wang, Ze‐Shu; Hou, Bo‐Shang; Zhang, Hao‐Wen; Deng, Chao; Ye, Long‐Wu (Angewandte Chemie International Edition, 2020)
6π electrocyclization has attracted interest in organic synthesis because of its high stereospecificity and atom economy in the construction of versatile 5–7‐membered cycles. However, examples of asymmetric 6π electrocyclization are quite scarce, and have to rely on the use of chiral organocatalysts, and been limited to pentadienyl‐anion‐ and triene‐type 6π electrocyclizations. Described herein is a zinc‐catalyzed formal [4+3] annulation of isoxazoles with 3‐en‐1‐ynol ethers via 6π electrocyclization, leading to the site‐selective synthesis of functionalized 2H‐azepines and 4H‐azepines in good to excellent yields with broad substrate scope. Moreover, this strategy has also been used to produce chiral 2H‐azepines with high enantioselectivities (up to 97:3 e.r.). This protocol not only is the first asymmetric heptatrienyl‐cation‐type 6π electrocyclization, but also is the first asymmetric reaction of isoxazoles with alkynes and the first asymmetric catalysis based on ynol ethers. A zinc‐catalyzed formal [4+3] annulation of isoxazoles and 3‐en‐1‐ynol ethers by 6π electrocyclization is reported, enabling divergent access to functionalized 2H‐azepines and 4H‐azepines in good to excellent yields with broad substrate scope. An asymmetric formal [4+3] annulation was also achieved to produce chiral 2H‐azepines with high enantioselectivities.